ANALISIS PERBEDAAN HASIL PENGUKURAN TEKANAN DARAH LENGAN KIRI DAN LENGAN KANAN PADA PENDERITA HIPERTENSI - Mery Solon (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2018)
The increase in the prevalence of hypertension is a serious threat to Indonesian’s health, because the effects of these conditions vary, it can be high in mortality and morbidity and consume a high cost of family for medications and make an economic burden. The purpose of this study is to determine the difference in blood pressure in the left arm and right in hypertensive patients. The design study is an observational Analitic comparative. The sampling method in this study is a non-probability sampling with a consecutive sampling technique. The number of respondents as many as 30 people. The instrument used is the observation sheet and aneroid blood pressure meter which is then analyzed using the Mann-Whitney test. Statistical test results showed that systolic blood pressure values ??and ? = 0.002 for diastolic pressure with the value ? = 0.026, which means the value of ? <? (0.05) so that it can be concluded that there are significant differences between the measurement of blood pressure in the left arm compared with the right arm, especially in patients with hypertension